Relative Value Units Underestimate Reimbursement for Revision Shoulder Arthroplasty. Issue 9 (1st May 2022) - Belay, Elshaday S.; Charalambous, Lefko T.; Saltzman, Eliana B.; Klifto, Christopher S.; Anakwenze, Oke
Abstract : Introduction: Relative value units (RVUs) have been fundamental to reimbursement calculations in payment models for arthroplasty surgeons. RVUs are based on various factors, including physician work, and have been higher for increased complexity, such as revision arthroplasty. The purpose of this study was to compare RVUs and estimated reimbursement differences between primary and revision shoulder arthroplasty. Methods: The National Surgical Quality Improvement Program database was used to collect primary and revision shoulder arthroplasty cases in 2017. Data variables collected included age at the time of surgery, surgical time, and RVU for each shoulder arthroplasty. Results: A total of 4, 948 shoulder arthroplasty patients (4, 657 primary and 291 revision) were included in this study. The mean age was 69.1 years (9.6 SD) for primary shoulder arthroplasty and 67.8 years (10.4 SD) for revision shoulder arthroplasty, P = 0.02. RVU for primary shoulder arthroplasty was 22.1 (0 SD) compared with 26.4 (1.1 SD) for revision shoulder arthroplasty ( P = 0.0001). Surgical time was significantly higher in revision versus primary cases, 131.5 minutes (89.0 SD) versus 109.3 minutes (42.5 SD) ( P = 0.0001). RVUs per minute were near equivalent for primary and revision arthroplasty at 0.20 (0.1 SD) and 0.20 (01 SD), respectively. However, owing to the difference in surgical time and cases per day, this translates to an estimated reimbursement difference of $174, 554.4 per year more for primary shoulder arthroplasty over revision cases. Conclusion: The current RVU model does not adequately factor surgical time for revision shoulder arthroplasty and translates to a notable yearly reimbursement difference that favors primary shoulder arthroplasty.